Phytochemistry and pharmacology of Curculigo orchioides Gaertn: A review - Pallishree Bhukta, Santosh Kumar Ranajit, Pratap Kumar Sahu, Deepankar Rath (Journal of Applied Pharmaceutical Science, 2023)
Curculigo orchioides Gaertn. is a rare rasayana herb (family Amaryllidaceae) popularly known as “Kali Musli”. Traditionally used in Ayurvedic medicine as an aphrodisiac and adaptogen, the plant is native to India. There is evidence that the plant contains mucilage, phenolic glycosides, saponins, and aliphatic compounds. This folk medicine can treat a wide range of ailments, including impotency, aphrodisiacs, tonics, jaundice, and skin conditions. There are also many scientists who have investigated its antioxidant, anticancer, and hepatoprotective properties. Curculigo was isolated for its chlorophenolic glucosides, curculigine, phenolic glycosides, orcinosides, and polysaccharides. As an herbal medicine, Curculigo’s quality can be controlled through new analyzing methods. Furthermore, Curculigo has been investigated for its pharmacological activity against diabetes, bacteria, inflammation, osteoporosis, oxidative stress, cancer, and neurodegeneration. Scientific methods were gradually developed for the application of herbal medicine. A more comprehensive pharmacological study of the genus Curculigo is needed to determine its medicinal value. An updated and comprehensive review of the medicinal plant C. orchioides Gaertn is presented here describing traditional uses, phytochemistry, pharmacology, and toxicology, and understanding its future research and development prospects.
Keywords: Curculigo orchioides, phytochemicals, pharmacological activity, Kali Musli, curculigoside